Biochemistry : molecules, cells, and the body - Dow, Jocelyn Lindsay, Gordon (Addison-Wesley, 1996)
Provides a concise and relevant presentation of the biochemistry required by medical students today, making the essential aspects of the subject in relation to the function of the body clear and understandable at every level.